PENGEMBANGAN INSTRUMEN LITERASI NUMERASI BERBASIS HOTS PADA MATERI ARITMATIKA SOSIAL - Pratiwi, Ulpha Mega; Yuhana, Yuyu (Jurnal Riset Pembelajaran Matematika, 2024)
The purpose of this research is expected to be able to foster numeracy literacy skills and HOTS skills, in this case which is raised by social arithmetic material. This research is a development research using a four-D (4D) model, conducted on June 3, 2024 for 32 grade VII junior high school students. The instrument developed consists of 4 descriptive questions. The results of this study show that HOTS-based numeracy literacy development questions can be used to support numeracy literacy with a validity test conducted by as many as 32 respondents. The results are based on the calculation of the r value > 0.349, for df = 32-2 = 30, α = 0.05, then the item is valid, the reliability value of the question is 0.63, showing that the level of the instrument developed meets the reliability aspect.